2016
DOI: 10.1002/anie.201608413
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Phenolic Supramolecular Gelation

Abstract: Materials assembled by coordination interactions between naturally abundant polyphenols and metals are of interest for a wide range of applications, including crystallization, catalysis, and drug delivery. Such an interest has led to the development of thin films with tunable, dynamic properties, however, creating bulk materials remains a challenge. Reported here is a class of metallogels formed by direct gelation between inexpensive, naturally abundant tannic acid and group(IV) metal ions. The metallogels exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
134
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(146 citation statements)
references
References 29 publications
2
134
1
5
Order By: Relevance
“…These substances have shown already remarkable properties as antioxidant, antibacterial, antimutagenic, and antitumor agents . Also, their complexation ability enables their functionalization with various metal ions . The usage of these unique properties combined in one molecule leads to great potential uses in biomedical science …”
Section: Introductionmentioning
confidence: 99%
“…These substances have shown already remarkable properties as antioxidant, antibacterial, antimutagenic, and antitumor agents . Also, their complexation ability enables their functionalization with various metal ions . The usage of these unique properties combined in one molecule leads to great potential uses in biomedical science …”
Section: Introductionmentioning
confidence: 99%
“…It suggests that broader absorption bands induced by metal‐linked hydrogen from TA enlarges the p‐electron delocalization in the conjugated system and thus changing the corresponding intrinsic optical/electronic properties . Based on above characterization and previous literatures, a scheme for this coordination complexation displayed that three OH groups in TA are deprotonated to generate active moieties induced by tribochemistry, and they are subsequently linked by Fe 3+ or Al 3+ and Ti 2+ or Cu 2+ , which originate from metal oxide surfaces, leading to form the TA‐M materials under tribochemistry.…”
Section: Resultsmentioning
confidence: 74%
“…Inspired by the coordination of polyphenols and metal ions and metal oxide layer,[32b,34] much effort has been dedicated to prepare the coatings for patterning, antifouling, and even forming the capsules via friction. Such ability to induce the films formation opens the possibility for the spatial control of phenolic coatings on different surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Caruso and co-workers recently showed that the coordination of tannic acid (TA) with metals enables the synthesis of av ariety of nanoscale and bulk substrates by simple wet chemistry. [28][29][30][31][32][33] This strategy has been employed for the synthesis of various types of multifunctional nanocapsules and combinatorial nanostructures.I nc ontrast, Messersmith and co-workers suggested that plant polyphenols (including TA)c an envelop various substrates without the need for coordination when employed as the sole coating precursor. [34] However,owing to alack of functionality,such systems have not been considered as photoresponsive systems to date even though such systems can be used to control various properties in both time and space.…”
Section: Dedicated To Professor Chulhee Kim On the Occasion Of His 60mentioning
confidence: 99%
“…[28][29][30][31][32][33] This strategy has been employed for the synthesis of various types of multifunctional nanocapsules and combinatorial nanostructures.I nc ontrast, Messersmith and co-workers suggested that plant polyphenols (including TA)c an envelop various substrates without the need for coordination when employed as the sole coating precursor. [28][29][30][31][32][33] This strategy has been employed for the synthesis of various types of multifunctional nanocapsules and combinatorial nanostructures.I nc ontrast, Messersmith and co-workers suggested that plant polyphenols (including TA)c an envelop various substrates without the need for coordination when employed as the sole coating precursor.…”
mentioning
confidence: 99%